Developmental Psychopathology 2016
DOI: 10.1002/9781119125556.devpsy105
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Models and Mechanisms for Understanding the Effects of Early Experiences on Psychological Development

Abstract: Understanding how and why early exposure to stress may have lasting effects on behavior and biology is fundamental to developmental study of psychopathology. Significant progress in this area has been made since the previous volume, in terms of the quality and quantity of findings and the types of research targets. This chapter reviews illustrative and intriguing findings in this large and diverse area of study. Key sections of the chapter aim to outline and differentiate leading developmental models for testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 384 publications
1
6
0
Order By: Relevance
“…Similar to the finding obtained in our study, these have been found to predict depression and anxiety in childhood and adolescence (e.g., Bufferd et al, 2014;Edwards et al, 2010;Kim et al, 2003;Luby et al, 2006) as well as membership of trajectory classes characterized by high internalizing symptoms (Weeks et al, 2014). Beyond this, our results support the notion that specifically early life events of loss/separation are risk factors for increasing or chronic internalizing symptoms (O'Connor, 2016), which, in turn, could be used to identify children at risk for an unfavorable development early on.…”
Section: Risk and Maintenance Factors For High Internalizing Trajectosupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to the finding obtained in our study, these have been found to predict depression and anxiety in childhood and adolescence (e.g., Bufferd et al, 2014;Edwards et al, 2010;Kim et al, 2003;Luby et al, 2006) as well as membership of trajectory classes characterized by high internalizing symptoms (Weeks et al, 2014). Beyond this, our results support the notion that specifically early life events of loss/separation are risk factors for increasing or chronic internalizing symptoms (O'Connor, 2016), which, in turn, could be used to identify children at risk for an unfavorable development early on.…”
Section: Risk and Maintenance Factors For High Internalizing Trajectosupporting
confidence: 91%
“…A number of studies report that stressful life events (e.g., loss of/separation from a significant person, transitions, and accidents) predict depression and anxiety both in childhood (Bufferd et al, 2014;Edwards, Rapee, & Kennedy, 2010;Furniss, Beyer, & Müller, 2009;Luby, Belden, & Spitznagel, 2006;Scheuer et al, 2016) and in adolescence (Kim, Conger, Elder, & Lorenz, 2003). Developmental studies offer strong support that stressful life events, especially in the first years of life, can exert protracted effects (for a review, see O'Connor, 2016). Similarly, the presence of maltreatment in early childhood has been highlighted as one of the most detrimental risk factors for an individual's psychosocial development (Cicchetti & Toth, 2015;Teicher & Samson, 2013).…”
Section: Social and Interpersonal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…life events). Among others, this issue overlaps with the core theoretical distinctions between early developmental programming vis-a-vis the influence of current context or cumulative stress (O'Connor, 2016) as well as the nature-nurture debate. For example, an ongoing line of inquiry within attachment research focuses on whether long-term effects of early maternal sensitivity on psychopathology persist mainly when quality of caregiving exhibits continuity or whether effects of early maternal sensitivity prevail even after taking concurrent caregiving contexts into account (see Fearon, Groh, Bakermans-Kranenburg, van Ijzendoorn, & Roisman, 2016).…”
mentioning
confidence: 99%
“…To tackle such questions, it is of great importance to conduct research beginning in early childhood where evidence for sensitive windows of development is considerable (O'Connor, ). In our laboratory, we have contributed to a growing evidence base showing that various preschool risk factors, ranging from parental psychopathology and peer victimization to temperamental factors and HPA axis dysregulation, are both concurrently and longitudinally related to patterns of internalizing symptoms and disorders (e.g.…”
mentioning
confidence: 99%